Distraction techniques in pediatric dentistry for the management of children from ages 5 to 10 years. Literature review - Cuya Garcia, Raysa Alejandrina (2023)
Objective: To review information related to distraction techniques used in pediatric dentistry for the management of children aged between 5 and 10 years. Mateial and Methods: The search strategy for literature was carried out in the following electronic databases: Scielo, Pubmed, Scopus and LILACS. The terms "methods", "distraction", "child", “child behavior”, “dental anxiety” and “pediatric dentistry” were used for search. The selection criteria included articles published from January 2017 and December 202 in Spanish and English languages. Observational studies and randomized clinical trials which reported distraction techniques in pediatric dentistry in managing children aged between 5 and 10 years were included. Results: The 3D audiovisual glasses, music, aromatherapy, and playful distraction were most used distractors in children from ages 5 to 10 years. These methods diminished children’s anxiety and fear; and they also improved or maintained a positive children’s behavior during dental treatments. Conclusion: Active distraction techniques such as 3D glasses (games or cartoons) and music therapy (happy or relaxing sounds) as well as passive distraction techniques such as aromatherapy, playful distraction and hypnosis are distractors methods for managing children from ages 5 to 10 years undergo dental treatment. Both passive and active techniques are equally efficient in terms of distraction and can reduce stress, fear, pain and anxiety in children.